AN INDIVIDUAL APPROACH IN THE DESIGN AND MANUFACTURE OF SHOES FOR PATIENTS WITH DIABETES - BABYCH АNTONINA; LYPSKI, TIMOFEY; LISCHUK, VIKTOR; ZLOTENKO, BORYS; MEREZHKO, NINA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Type 2 diabetes is a disease that occurs in people at different ages when the body cannot produce and use insulin in sufficient quantities. Therefore, the disease is chronic and complex, since various organs and systems are affected at the same time. Special shoes and insoles are one of the means to combat this phenomenon. Such shoes create a comfortable environment in the middle of the product and protect the feet as much as possible from dangerous environmental factors. This work describes general information about the disease of diabetes, about the diabetic foot, about what shoes should be for type 2 diabetes, the main requirements, distinguishing features, and design features of orthopedic shoes of this subgroup. A step-by-step description of the stages of work on the manufacture of shoes for this purpose is presented, taking into account the customer’s foot pathology in type 2 diabetes, factors of comfort and aesthetics. The work uses the following methods: organoleptic observations and measurements of feet, analysis of initial medical information regarding the diagnosis of the patient’s feet, manual preparation and augmentation of certain segments of the shoe, development of the model design, as well as the manufacture of shoes by individual order under the conditions of Litini LLC. The individual project of orthopedic shoes is made taking into account the medical component in accordance with the diagnosis and recommendations of the endocrinologist, as well as taking into account the customer’s requirements for functionality, ergonomics and aesthetics. As a result, ready-made shoes and a package of design and technological documentation for the product are presented. The manufactured shoes were tested in the conditions of daily experimental wearing of the product by the customer, which allowed to confirm the high quality of the product, to affirm the possibility of effective combination of the functional constructive component of this orthopedic shoe with the current aesthetic design.